Analysing the impact of collaborations between airlines and maintenance service company under MRO outsourcing mode: Perspective from airline's operations. (June 2023) - Qin, Yichen; Ng, Kam K.H.
Abstract: The practice of Aircraft Maintenance Repair and Overhaul (MRO) outsourcing has changed airline companies' decision-making processes in both operational and tactical levels. Specifically, the aircraft heavy maintenance service provided by an independent maintenance service company alleviates airlines' fixed-asset investments and daily operations regarding maintenance. On the other hand, the fluctuations in MROs service capability, availability and service level also affect airlines' fleet management and daily operations if their maintenance demands cannot be met in a timely manner. In this regard, the impact of the collaborations between airlines and maintenance service company is investigated from the perspective of airline's operations, by studying the maintenance planning problem at operational level. Afterwards, to examine and investigate the impact of collaborations between the two parties have on airline's operational performance, aircraft maintenance routing problems under 'airlines-service company' non-collaborative and collaborative contexts are investigated and formulated. The computational results demonstrate the effectiveness of the MRO collaboration under outsourcing mode, in view of airline company's overall operational revenue and flexibility while carrying out maintenance routing for individual aircraft in its fleet. Highlights: The impact of MRO collaboration establishment between airline and MRO service company is addressed in this paper. The effects of collaboration under MRO outsourcing mode are investigated from airline's perspective. Aircraft maintenance routing problems are studied and modelled from non-collaborative and collaborative contexts. Computational experiment is carried out to comprehend the impact of MRO collaboration. The effects of maintenance service priority variations are analyzed, followed by the managerial insights.